(untitled) (African Journal of Public Administration & Management, 2026)
Building resilience in public organizations is crucial for maintaining function during disruptions, fostering adaptability, and ensuring long-term success. It allows these organizations to absorb shocks, recover from crises, and even find opportunities for growth amidst uncertainty, which strengthens public trust and improves service delivery. Young professionals possess the critical energy, creativity, and adaptability which make them uniquely equipped to address pressing global and organizational challenges of our time.